Plasmonic metamaterials based on titanium oxides - Vukoman Jokanović; Božana Čolović; Bojan Jokanović; Stevan Stojadinović; Ilija Nasov (Zaštita Materijala, 2016)
The basic information about any kind of metamaterials is given in this paper. Special attention is dedicated to materials on the base of titanium oxides, which have not been studied as metamaterials yet. Due to different titanium oxidative states in thin films of titanium oxides deposited by dc magnetron sputtering, which influence various conductive properties from the ones typical for dielectrics, over the ones typical for semiconductors, to the ones typical for metalloids, these materials show typical metamaterials properties. This is noticed for the first time in our investigations, which are partially presented in this paper. Huge number of band gaps influences extreme change of optical properties, particularly refractive index which changes from very high to near zero values. Reasons for that behaviour are explained over corresponding splitting of molecular orbitals.